Respuesta :
For this case, what we must do is apply the following rule for the function g (x):
g (x) = -f (x) - 2
We have then:
For x = -2:
g (-2) = -f (-2) - 2
g (-2) = - (- 1) - 2
g (-2) = 1 - 2
g (-2) = -1
For x = -1:
g (-1) = -f (-1) - 2
g (-1) = - (1) - 2
g (-1) = -1 - 2
g (-1) = -3
For x = 0:
g (0) = -f (0) - 2
g (0) = - (3) - 2
g (0) = -3 - 2
g (0) = -5
For x = 1:
g (1) = -f (1) - 2
g (1) = - (5) - 2
g (1) = -5 - 2
g (1) = -7
Answer:
the table for function g is:
x -2 -1 0 1
g(x) -1 -3 -5 -7
g (x) = -f (x) - 2
We have then:
For x = -2:
g (-2) = -f (-2) - 2
g (-2) = - (- 1) - 2
g (-2) = 1 - 2
g (-2) = -1
For x = -1:
g (-1) = -f (-1) - 2
g (-1) = - (1) - 2
g (-1) = -1 - 2
g (-1) = -3
For x = 0:
g (0) = -f (0) - 2
g (0) = - (3) - 2
g (0) = -3 - 2
g (0) = -5
For x = 1:
g (1) = -f (1) - 2
g (1) = - (5) - 2
g (1) = -5 - 2
g (1) = -7
Answer:
the table for function g is:
x -2 -1 0 1
g(x) -1 -3 -5 -7
Answer:
the table for function g is:
x -2 -1 0 1
g(x) -1 -3 -5 -7
Step-by-step explanation: